The effect of using the project-based learning (pbl) strategy on female student attitudes towards the subject of Physical education - Alawrtani, Maha Ahmad (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to reveal the impact of using the project-based learning strategy on students’ attitudes, specifically towards the subject of physical education, among seventh-grade female students in public schools in Aqaba. To achieve the study objectives, the experimental approach with a quasi-experimental design was used, by distributing the research group into two groups, one of which was experimental and consisted of (25) female students who studied physical education using the project-based learning strategy, and the other was a control group consisting of (25) female students who studied the same subject using the traditional method. By applying the study tool (scale) to both research groups (experimental and control), the results of the study showed a general trend towards high acceptance of this strategy. It also showed that the use of the project-based learning strategy increases the happiness of female students in teaching physical education, develops thinking and creativity, and stimulates activity and enthusiasm among them. The study also recommends the necessity of enhancing the training of physical education teachers on the mechanisms of practical application of this strategy due to its positive impact on teaching various educational subjects, specifically physical education.